Pengaruh Kualitas Internet Banking, Mobile Banking Dan Automatic Teller Machine (Atm) Terhadap Kepuasan Nasabah (Studi Kasus Pada Bank BRI KCP Tumpang) - Misbakhus Sudur; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to assess and analyze the impact of Internet Banking, Mobile Banking, and ATM services on customer satisfaction at Bank BRI KCP Tumpang. This is a quantitative study. Customers who utilize the Internet Banking, Mobile Banking, and ATM facilities at Bank BRI KCP Tumpang comprise the study's population. In this investigation, a basic random sample procedure was applied. A questionnaire was used to collect data for this investigation. Data analysis approaches use quantitative methodologies, namely multiple linear regression analysis with a significance threshold of 0.05. The F test findings reveal that Internet Banking, Mobile Banking, and ATMs all have a favorable and substantial influence on Customer Satisfaction at Bank BRI KCP Tumpang. Based on the coefficient of determination (R2) test, the corrected R Square value is 0.635, indicating that Internet Banking, Mobile Banking, and ATM can explain 63.5% of the Customer Satisfaction components. The remaining 36.5% is explained by factors not investigated in this study. Keywords: Internet Banking, Mobile Banking, ATM Facilities And Customer Satisfaction.